Pengaruh Aktivitas Diskusi Kelas Terhadap Kemampuan Penguasaan Materi Pembelajaran Statistik pada Mahasiswa Akuntansi Syariah - Siregar, Rizka Fahruza; Ramadhani, Rini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the influence of classroom discussion activities on the ability to master statistical learning materials in sharia accounting students. The method used in this study is quantitative, with data collection through a questionnaire distributed to 19 respondents. The data analysis technique used is multiple linear regression. The results of the analysis showed that there was a significant positive relationship between class discussion activities and material mastery ability. This study indicates that the application of the discussion method can improve students' understanding of statistical materials, as well as encourage critical and analytical thinking skills. These findings make an important contribution to the development of more effective learning strategies in the academic environment.